Technological perspectives of Metaverse for financial service providers - Ahmet Faruk Aysan (11902115) (2024)
Most banking institutions are inadequately prepared for the ongoing integration of technology, including the digitalization of financial services, the advent of the Metaverse, and the emergence of Web 3.0. While other sectors are making strides in navigating virtual environments, financial institutions appear to be trailing. Concurrently, the nascent ecosystem of the Metaverse presents promising opportunities for businesses and industries, potentially revolutionizing economic models, governance frameworks, and ethical paradigms. This study aims to contribute to the emerging discourse on the provision of financial services within the Metaverse. The paper envisages virtual reality's future financial services landscape using a scenario-based technological foresight approach. This research is the first attempt to map the comprehensive landscape of financial services in the Metaverse, both in the present context and the foreseeable future. The paper delineates the economy of the Metaverse, its key sectors, and its enablers. It overviews the initial experiences with virtual financial services and proposes potential prospects for financial institutions operating within the Metaverse. This study, therefore, serves as a foundational reference for understanding the evolving dynamics of financial services in the virtual realm. Other Information Published in: Technological Forecasting and Social Change License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.techfore.2024.123323